Room-temperature sodium-ion batteries : Improving the rate capability of carbon anode materials by templating strategies - Wenzel, Sebastian; Hara, Takeshi; Janek, Jürgen; Adelhelm, Philipp; Justus Liebig University Giessen (My University, 2011)
Current kinetic limitations of carbon anode materials in sodium-ion batteries can be effectively tackled by using tailor-made carbon materials with hierarchical porosity prepared via the nanocasting route. Capacities exceeding 100 mA h g-1 at C/5 are found while exhibiting excellent rate capability and reasonable cycle life.
Keywords: ddc:530